A review of electrocatalysts with enhanced CO tolerance and stability for polymer electrolyte membarane fuel cells - Ehteshami, Seyyed Mohsen Mousavi (2013)
A comprehensive review of the investigations performed in search for development of electrocatalysts with enhanced reformate tolerance for low temperature polymer electrolyte membrane (PEM) fuel cells are presented. Remarkable efforts have been made to attain improved catalytic activities and robustness by adding second element to Pt/C or third element to Pt–Ru/C, commercial catalysts for PEM fuel cell applications. The enhanced CO tolerance of the developed catalysts is strongly dependent on the type, composition and atomic ratios of the added elements/groups, and type and structure of the support materials. The synthesis method of the catalysts also plays a remarkable role in the catalytic activity and stability since it determines the structure, morphology and size distribution of the catalyst nanoparticles, which are directly effective on the stability and activity. Choosing a proper synthesis method, inclusion of appropriate content of suitable promoters to Pt-based catalysts, and using a proper support material are the major requirements of an effective catalyst. The CO tolerance enhancement has been attributed to the bi-functional mechanism and electronic effects. Understanding the underlying mechanisms and the activity–structure correlations will shed a light in designing novel electrocatalysts via innovative routes for excellent robust CO tolerant electrocatalysts.